Carbon-coated one-dimensional ferrous fluoride positive electrode material and preparation method and application thereof
By using the preparation method of carbon coating one -dimensional fluoride sub -iron positive material, the existing lithium -ion battery positive electrode material reversed comparison capacity and FEF2 positive pole material high insulatability and voltage lag, and realized the high ion battery high Electrochemical properties and cycle stability.
Patent Information
- Application Number
- CN202211173389.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The reversible specific capacity of existing lithium-ion battery cathode materials is low, making it difficult to meet the growing battery life requirements of electric vehicles and electronic equipment. At the same time, the FeF2 cathode materials exhibit high insulation and voltage hysteresis when commercially used, resulting in battery energy conversion efficiency and utilization efficiency. reduce.
Use a carbon to cover one -dimensional fluoride sub -iron positive material. By mixing iron powder or soluble metal iron salt with fluorosalicate solution, after stirring reaction, centrifugal separation and steaming to obtain fluorine siliconized ferrous iron powder, and then polyethylene. Pyrodermine is mixed, preparation of static spinning method, and carbonized in an inert atmosphere in air or oxygen in air or oxygen, prepares carbon with good electrical and structural stability to cover one -dimensional fluorine sub -iron positive material.
The carbon -dimensional fluorine sub -iron positive material is significantly improved, which significantly improves the electrochemical properties of the battery, including the first discharge ratio capacity and cycle stability, and overcomes the problem of high insulation and voltage lag of Fef2 positive pole materials during commercial use. The energy conversion efficiency and utilization efficiency of the battery.
Smart Images

Figure CN115411253B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery preparation, and in particular to a carbon-coated one-dimensional ferrous fluoride positive electrode material and a preparation method and application thereof. Background Art
[0002] The key to the development of electric vehicles lies in batteries. Among the existing secondary batteries, the theories and processes of lead-acid batteries, cadmium nickel batteries (Cd / Ni), metal hydride nickel batteries (MH / Ni) and lithium-ion batteries (LIBs) are relatively mature and have been commercially applied. In contrast, the lithium-ion battery process is relatively mature and has the advantages of high energy density, high operating voltage, long cycle life, no memory effect, small size, light weight and low environmental pollution. Therefore, the power batteries of electric passenger vehicles are mainly lithium-ion batteries, such as Tesla's ternary lithium-ion battery (NCR18650) and BYD's lithium iron phosphate battery (LFP). At the same time, as a type of chemical battery with excellent performance, lithium-ion batteries are not only in great demand in the field of electric vehicles, but are also used in various small portable electronic devices (such as digital cameras, smart phones and laptops, etc.) as well as submarines, aerospace, aviation, grid-scale energy storage systems (ESS), etc. Therefore, if safe and high-performance lithium-ion batteries are developed, they will have a very broad application prospect.
[0003] Theoretically, there are two main ways to increase the energy density of batteries: one is to increase the specific capacity of the positive and negative electrode materials; the other is to increase the working voltage between the positive and negative electrodes. The positive electrode material of lithium-ion batteries is an important component of the battery. As a lithium source, it directly participates in the electrode reaction and accounts for about 40% of the cost of lithium-ion batteries. Therefore, the properties of the positive electrode material directly determine the performance and cost of secondary lithium-ion batteries. Important progress has been made in the negative electrode materials of lithium-ion batteries. They are abundant in source and cheap in price. In contrast, the positive electrode materials have developed slowly. Therefore, current research on improving the density of lithium-ion batteries is mainly focused on the positive electrode materials of batteries. The positive electrode materials of batteries are required to have large theoretical specific volume capacity and specific mass capacity, stable structure, and no drastic volume changes during the cycle. However, according to the current status of the lithium battery industry, the intercalation materials (such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 ,LiNi 1-x-y Co x Mn y O 2Their reversible specific capacity is usually less than 200mA.h / g. Even in the high-nickel ternary material system, 300W.h / kg is the maximum energy density that can be achieved by lithium-ion secondary batteries currently developed by most new energy vehicle companies. Therefore, they are difficult to meet the growing endurance requirements of today's electric vehicles and electronic devices.
[0004] Transition metal fluoride (denoted as MF x , M=Fe, Cu, Ni and other transition metals) have strong ionic bonds, and the electrodes prepared with them will have a large electromotive force, which makes the battery energy density higher. In addition, the electrode preparation does not require the use of elements such as cobalt and nickel, so the cost is lower and more environmentally friendly. Therefore, transition metal fluorides have received widespread attention in recent years. 2 Although it has many advantages, its band gap is very strong, which gives FeF 2 The higher electrochemical potential also makes the material highly insulating, so FeF 2 The electrochemical performance of the cathode material was not good when it was first commercialized. In the voltage test range of 2.0 to 4.5 V, the -2 At a current density of only 140 mAh g -1 and 80mAh g -1 The actual first discharge specific capacity and stable reversible specific capacity of FeF 2 In the experiment, the cathode material also observed obvious voltage hysteresis, which would reduce the energy conversion efficiency and utilization efficiency of the battery, and FeF 2 The electrodes will also react with the electrolyte. For example, after the positive electrode is actively dissolved in the organic electrolyte, it will reprecipitate, eventually causing a series of side effects such as capacity decay and reduced battery rate performance. At the same time, the volume change during lithium insertion and delithiation will produce internal stress, thereby inducing expansion and decomposition of the electrode structure, separation of the electrode and the current collector, crushing of active particles, and formation of cracks and defects on the protective shell and SEI layer. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon-coated one-dimensional ferrous fluoride positive electrode material and its preparation method and application in view of the above-mentioned problems. The positive electrode material of the present invention has a carbon matrix with good conductivity, which can play a confining role and thus protect FeF 2 The nano-grain structure enhances electrode stability and conductivity, overcoming the shortcomings of existing technologies.
[0006] The technical solution adopted by the present invention is as follows: A method for preparing a carbon-coated one-dimensional ferrous fluoride positive electrode material comprises the following steps:
[0007] A. Mix iron powder or soluble ferrous salt with fluorosilicic acid aqueous solution or fluorosilicate solution (CuSiF 6 ) are mixed, stirred for reaction, and the supernatant is separated by centrifugation and evaporated to dryness to obtain ferrous fluoride silicic acid powder;
[0008] The chemical reaction formula between iron powder and fluorosilicic acid aqueous solution is:
[0009] Fe+H 2 SiF 6 →FeSiF 6 6H 2 O+H 2 ↑
[0010] For fluorosilicate solution, CuSiF 6 For example, ferrous fluoride silicide powder can be prepared by replacing copper with iron powder;
[0011] B. dissolving ferrous fluoride silicic acid powder and polyvinyl pyrrolidone in a solvent according to a mass ratio, and mixing them evenly to obtain a viscous mixed solution;
[0012] C. Using the mixed solution obtained in step B as an electrospinning solution, preparing an electrospinning material by an electrospinning method;
[0013] D. The electrospinning material obtained in step C is placed in air or oxygen for pre-oxidation, then carbonized in an inert atmosphere, and finally taken out.
[0014] In the present invention, polyvinyl pyrrolidone, as a conjugated polymer, has good electrical conductivity and mechanical properties, and structurally builds a bridge between polymers and metals, so it can be used as an excellent carrier of transition metal fluorides to enhance the electrical conductivity and structural stability of transition metal fluorides. Without introducing an additional fluorine source, the present invention uses liquid phase reaction to synthesize precursors, electrospinning composites and high-temperature solid phase reactions to embed transition metal fluorides into conjugated polymers, and uses the nano properties, electrical conductivity and structural toughness of one-dimensional carbon materials to improve the electrochemical activity, intrinsic conductivity and structural stability of transition metal fluorides, thereby comprehensively improving the electrochemical properties of transition metal fluorides.
[0015] Furthermore, in the above step A, soluble ferrous salts such as ferrous chloride, ferrous nitrate, etc. can be directly used. Taking ferrous chloride as an example, FeCl can be added to the hydrofluorosilicic acid aqueous solution. 2 Mixed reaction, the reaction equation is:
[0016] FeCl 2 +H 2 SiF 6 6H 2 O→FeSiF6 6H 2 O+HCl
[0017] Then, the obtained HCl is volatilized out by evaporating the solution to obtain ferrous fluoride silicide powder.
[0018] Furthermore, in step A, the molar ratio of iron powder to fluorosilicic acid is 1-2:1, that is, an excess of iron powder is required to ensure that H 2 SiF 6 6H 2 O is completely reacted, and the molar ratio can be 1.1:1, 1.12:1, 1.15:1, 1.18:1, 1.2:1, 1.21:1, 1.25:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 2:1, etc.
[0019] Furthermore, in step A, the evaporation temperature when evaporating the filtrate is 50-150°C, for example, it can be 50°C, 60°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.
[0020] Preferably, in order to facilitate subsequent electrospinning, in step B, the solvent is ethanol water, and the mass fraction of ethanol in the ethanol water is 15-30%, for example, it can be 15%, 18%, 20%, 25%, 26%, 27%, 28%, 30%, etc.
[0021] Furthermore, in step B, the mass ratio of ferrous fluoride silicone powder to polyvinyl pyrrolidone is 1-2:1-2, for example, it can be 1:1, 1.1:1, 1.2:1, 0.9:1, 0.8:1, etc. The mass ratio of ferrous fluoride silicone powder to polyvinyl pyrrolidone is preferably within this range. If PVP (polyvinyl pyrrolidone) is excessive, part of the activity will be completely encapsulated in the PVP-derived carbon matrix, making it difficult to participate in the electrochemical reaction, resulting in a low battery capacity. Insufficient PVP makes it difficult to ensure the viscosity of the solution, resulting in the inability to spin the spinning solution. Through experiments, it is concluded that the optimal mass ratio of ferrous fluoride silicone powder to polyvinyl pyrrolidone is 1:1.
[0022] Furthermore, in order to obtain an electrospinning solution with suitable viscosity, in step B, the total mass fraction of ferrous fluoride silicofluoride powder and polyvinyl pyrrolidone in the mixed solution is 20-40%, for example, it can be 20%, 25%, 26%, 27%, 28%, 30%, 32%, 35%, 40%, etc.
[0023] Further, in step C, the pre-oxidation temperature is 200-300°C, for example, 200°C, 220°C, 230°C, 240°C, 250°C, 260°C, 280°C, 300°C, etc., and the carbonization temperature is 400-600°C, for example, 400°C, 450°C, 460°C, 470°C, 480°C, 500°C, 520°C, 530°C, 540°C, 550°C, 580°C, 600°C, etc. The pre-oxidation temperature should not be too high, as too high a temperature will cause FeF 2 Correspondingly, the carbonization temperature should not be too high. Too high a carbonization temperature will cause FeF 2 The grains grow coarseningly, changing from nanoparticles to micron particles, thereby reducing the battery capacity.
[0024] Furthermore, in step C, the heating rate during pre-oxidation is 0.1-1°C / min, and the heating rate during carbonization is 0.5-2°C / min.
[0025] Furthermore, the present invention also includes a carbon-coated one-dimensional ferrous fluoride positive electrode material, and the positive electrode material is prepared by the above-mentioned preparation method.
[0026] Furthermore, the present invention also includes an application of a carbon-coated one-dimensional ferrous fluoride positive electrode material in a lithium-ion battery, wherein the positive electrode material of the lithium-ion battery is the above-mentioned carbon-coated one-dimensional ferrous fluoride positive electrode material.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. The present invention utilizes the characteristics of polyvinyl pyrrolidone to build a bridge between polymers and metals, and uses it as an excellent carrier of transition metal fluorides, thereby enhancing the conductivity and structural stability of transition metal fluorides;
[0029] 2. The present invention performs pre-oxidation treatment on the electrospinning material. The pre-oxidation of PVP precursor is a crucial intermediate process in the production of PVP-based carbon fibers. It is a transitional stage from precursor to carbon fiber, but it becomes a key stage that affects the excellent performance of the final carbon fiber. The purpose of pre-oxidation is to transform the thermoplastic linear PVP precursor macromolecular chain into a non-plastic trapezoidal pre-oxidized fiber with a heat-resistant structure, so that it will not be destroyed during high-temperature carbonization. Its non-flammable and non-melting properties are conducive to maintaining the stable morphology and thermodynamic stability of the fiber, laying the foundation for further transformation into high-performance carbon fibers with a chaotic graphite structure. The pre-oxidation of PVP-based carbon fibers is generally completed in air at 220-250°C. By controlling the pre-oxidation time and then adjusting the pre-oxidation temperature during this process, the molecular chains of PVP can undergo chemical reactions moderately, and the linear molecular chains are cyclized and cross-linked to form a ladder-shaped structure that can be stable during high-temperature carbonization.
[0030] 3. The present invention utilizes liquid phase reaction to synthesize precursors, electrospinning composite and high temperature solid phase reaction to embed transition metal fluorides into conjugated polymers without introducing additional fluorine sources, and utilizes the nano properties, conductivity and structural toughness of one-dimensional carbon materials to improve the electrochemical activity, intrinsic conductivity and structural stability of transition metal fluorides, thereby comprehensively improving the electrochemical properties of transition metal fluorides. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a SEM image of the positive electrode material obtained in Example 1 of the present invention;
[0032] Figure 2 is a charge and discharge curve diagram of a lithium-ion battery assembled from the positive electrode material obtained in Example 1 of the present invention at a rate of 0.1C;
[0033] Figure 3 This is a cycle performance diagram of a lithium-ion battery assembled from the positive electrode material obtained in Example 1 of the present invention at 0.1C. DETAILED DESCRIPTION
[0034] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0036] Example 1
[0037] A method for preparing a carbon-coated one-dimensional ferrous fluoride positive electrode material comprises the following steps:
[0038] S1. Mix 2.4 g of reduced iron powder (CAS 7439-89-6) and 15.34 g of fluorosilicic acid aqueous solution (H 2 SiF 6 , CAS16961-83-4) were mixed and stirred at room temperature for 24 hours to obtain ferrous fluoride silicide (FeSiF 6 6H 2 O) aqueous solution and excess Fe precipitation;
[0039] S2, FeSiF 6 6H 2 O aqueous solution was centrifuged to separate the upper light green clear liquid, which was evaporated to dryness at 110 °C to obtain the light green FeSiF 6 6H 2 O powder;
[0040] S3, light green FeSiF 6 6H2 O powder and polyvinyl pyrrolidone (PVP) were dissolved in an ethanol water solution (containing 20 wt% ethanol) at a mass ratio of 1:1 and mixed to prepare a 30 wt% FeSiF 6 6H 2 Viscous solution of O / PVP;
[0041] S4, FeSiF 6 6H 2 FeSiF was prepared by electrospinning O / PVP solution 6 6H 2 O / PVP material; wherein, the electrospinning parameters are: voltage 20 kV, spinning distance 15 cm;
[0042] (5) FeSiF 6 6H 2 The O / PVP material was pre-oxidized in air at 250°C and 0.5°C / min, and then carbonized in argon at 500°C and 1°C / min for 1 h to obtain FeF 2 / C positive electrode material.
[0043] FeF prepared in Example 1 2 SEM images of / C cathode materials Figure 1 As shown, in Figure 1 The composite fiber has a diameter of about 150-200nm, and its interior is FeF with a particle size of about 10-25nm. 2 Nanoparticles, PVP-derived carbon matrix as FeF 2 The carrier and protective layer of the nanoparticles can inhibit the volume expansion and structural collapse that occur during the conversion reaction, while improving the conductivity of the active material.
[0044] Assembly of CR2025 button battery: The positive electrode material prepared in the above embodiment 1 is used as the positive electrode active material, the positive electrode active material is mixed with acetylene black and PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, NMP (N-methylpyrrolidone) is added and ground into a slurry, which is coated on an aluminum foil with a scraper, dried, and cut into positive electrode sheets; then assembled into a CR2025 button half-cell in an argon glove box (water <0.01ppm, oxygen <0.01ppm), wherein the positive electrode is the above positive electrode sheet, the counter electrode is a lithium sheet, the diaphragm is Celgard 2500, and the electrolyte is dimethyl carbonate, diethyl carbonate, and ethyl carbonate in a volume ratio of 1:1:1 as solvent, with 1 mol / L LiPF 6 A solution made of a solute.
[0045] The electrochemical performance test results are as follows Figure 2 and Figure 3 As shown, Figure 2The charge and discharge voltage capacity curves of the carbon-coated one-dimensional ferrous fluoride cathode material at a current density of 100 mA / g in the first, second and fifteenth cycles are shown. Figure 2 It can be obtained that its first discharge specific capacity is 514.87 mAh / g, which is close to its theoretical specific capacity of 572 mAh / g. After that, due to the formation of electrolyte interface film (CEI) and irreversible by-products, the second discharge specific capacity is reduced to 291.40 mAh / g, but after 15 times, the discharge specific capacity is still 293.28 mAh / g, which shows that the material has good stability.
[0046] further, Figure 3 This is the capacity cycle number graph of the carbon-coated one-dimensional ferrous fluoride positive electrode material after 100 cycles at a current density of 100mA / g. It can be found that the discharge specific capacity gradually increases to 359.97mA / g in the first 30 cycles, which corresponds to the activation process of the active material and the electrolyte embedded in the carbon fiber, and then the capacity remains stable, which confirms the advantages of the PVP-derived carbon matrix in effectively inhibiting the volume change of the active material and stabilizing the crystal structure, ultimately allowing the one-dimensional ferrous fluoride positive electrode material to exhibit good discharge specific capacity and cycle stability.
[0047] Example 2
[0048] Example 2 is the same as Example 1, except that the fluorosilicic acid aqueous solution is replaced with a copper fluorosilicate solution.
[0049] Example 3
[0050] Example 3 is the same as Example 1, except that polyvinyl pyrrolidone is replaced by polyacrylonitrile (PAN) (PAN is insoluble in water and requires DMF as a solvent).
[0051] Comparative Example 1
[0052] Comparative Example 1 is the same as Example 1, except that there is no pre-oxidation process to obtain FeSiF 6 6H 2 After O / PVP material, carbonization treatment is carried out directly.
[0053] Comparative Example 2
[0054] Comparative Example 2 is the same as Example 1, except that the pre-oxidation temperature is 400°C.
[0055] Comparative Example 3
[0056] Comparative Example 3 is the same as Example 1, except that the carbonization temperature is 800°C.
[0057] Comparative Example 4
[0058] Comparative Example 4 adopts the preparation method of lithium battery thin film positive electrode material disclosed in Chinese patent CN114530593A to prepare ferrous fluoride positive electrode material, wherein the mass ratio of the composite material, the conductive agent (acetylene black) and PVDF is 8:1:1, and the mass ratio of carbon fiber to ferrous fluoride in the composite material is the same as that in Example 1.
[0059] Comparative Example 5
[0060] Comparative Example 5 is the same as Example 1, except that FeSiF 6 6H 2 The mass ratio of O powder to polyvinyl pyrrolidone is 1:3.
[0061] Comparative Example 6
[0062] Comparative Example 6 is a nano-FeF without any modification treatment. 2 , and use it as a positive electrode active material.
[0063] The electrochemical performance tests were conducted on the above-mentioned Examples 1-4 and Comparative Examples 1-6. The test results are shown in Table 1:
[0064] Table 1 Electrochemical performance of lithium ion batteries assembled from Examples 1-4 and Comparative Examples 1-5
[0065]
[0066]
[0067] It can be seen from Table 1 that the one-dimensional ferrous fluoride positive electrode material of the present invention exhibits good discharge specific capacity and cycle stability. Among them, the use of fluorosilicic acid aqueous solution performs better in terms of cycle stability. When polyvinyl pyrrolidone is replaced by PAN, the charge specific capacity is significantly improved, but the cycle stability is significantly reduced, indicating that the use effect of PAN is not as good as that of polyvinyl pyrrolidone.
[0068] Further, it can be obtained from Comparative Example 1 that when no pre-oxidation treatment is performed, the cycle stability of the positive electrode material is extremely poor, indicating that the pre-oxidation treatment can improve its cycle stability performance; it can be obtained from Comparative Example 2 that when the pre-oxidation temperature is too high, it not only fails to improve the cycle stability of the material, but will continue to deteriorate its cycle stability performance; it can be obtained from Comparative Example 3 that when the carbonization temperature is too high, the charge and discharge specific capacity of the positive electrode material decreases significantly, indicating that the carbonization temperature will affect the charge and discharge specific capacity of the positive electrode material; it can be obtained from Comparative Example 4 that the positive electrode material obtained by the patented technology has the same electrochemical performance as the positive electrode material prepared by the present application, and the positive electrode material prepared by the present invention is slightly better than the positive electrode material prepared by the patented technology in terms of cycle stability; it can be obtained from Comparative Example 5 that when polyvinyl pyrrolidone is excessive, the charge and discharge specific capacity and cycle stability of the positive electrode material are significantly reduced, which indicates that the amount of polyvinyl pyrrolidone used has a greater impact on the electrochemical performance of the positive electrode material. It can be obtained from Comparative Example 6 that when using nano-FeF without any modification treatment, the positive electrode material prepared by the present invention is slightly better than the positive electrode material prepared by the patented technology in terms of cycle stability. 2 Although its specific capacity is high, its cycle stability is extremely poor, making it difficult to achieve industrial application.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated one-dimensional ferrous fluoride positive electrode material, characterized in that: The following steps are involved: A. Mixing iron powder or soluble ferrous salt with fluorosilicic acid aqueous solution or fluorosilicate solution, stirring for reaction, centrifuging and separating the supernatant, and evaporating to dryness to obtain ferrous fluoride silicic acid powder; B. dissolving ferrous fluoride silicic acid powder and polyvinyl pyrrolidone in a deionized water solution of ethanol at a mass ratio of 1-2:1-2, and mixing them evenly to obtain a viscous mixed solution; C. Using the mixed solution obtained in step B as an electrospinning solution, preparing an electrospinning material by an electrospinning method; D. The electrospinning material obtained in step C is placed in air or oxygen for pre-oxidation, and then carbonized in an inert atmosphere. The pre-oxidation temperature is 200-300° C., and the carbonization temperature is 400-600° C. Finally, the electrospinning material is taken out.
2. The preparation method according to claim 1, characterized in that In step A, the molar ratio of iron powder to fluorosilicic acid is 1-2:
1.
3. The preparation method according to claim 1, characterized in that: In step A, the evaporation temperature when evaporating the filtrate is 50-150°C.
4. The preparation method according to claim 1, characterized in that: In step B, the deionized water solution of ethanol is ethanol water, and the mass fraction of ethanol in the ethanol water is 15-30%.
5. The preparation method according to claim 1, characterized in that: In step B, in the mixed solution, the total mass fraction of ferrous fluoride silicic acid powder and polyvinyl pyrrolidone is 20-40%.
6. The preparation method according to claim 1, characterized in that: In step C, the heating rate during pre-oxidation is 0.1-1°C / min, and the heating rate during carbonization is 0.5-2°C / min.
7. A carbon-coated one-dimensional ferrous fluoride positive electrode material, characterized in that: The positive electrode material is prepared by the preparation method described in any one of claims 1 to 6.
8. Application of a carbon-coated one-dimensional ferrous fluoride cathode material in a lithium-ion battery, characterized in that: The positive electrode material of the lithium-ion battery is the carbon-coated one-dimensional ferrous fluoride positive electrode material as described in claim 7.
Citation Information
Patent Citations
Lithium battery, lithium battery film positive electrode material and preparation method of lithium battery film positive electrode material
CN114530593A
Method of manufacturing a positive electrode active material of a secondary battery
CA2331602A1
Preparation method of lithium ferrous silicate composite material
CN103259019A
Cited By
Heteroatom-doped carbon-coated NiF2-based positive electrode material and preparation method and application thereof
CN120048878A